Second harmonic imaging of intrinsic signals in muscle fibers in situ - Both, Martin; Vogel, Martin; Friedrich, Oliver; Wegner, Frederic von; Künsting, Thomas; Fink, Rainer; Uttenweiler, Dietmar (Journal of biomedical optics, 2004)
We use second harmonic generation (SHG) imaging to study and quantify a strong intrinsic SHG signal in skeletal muscle fiber preparations and single isolated myofibrils. The intrinsic signal follows the striation pattern of the muscle cells and is positioned at the sarcomeric location of the myosin filaments. Interestingly, the signal is enhanced at the region where the myosin heads are located on the myosin filaments. As the intrinsic signal reflects the subcellular structure in an accurate way, SHG can be used for noninvasive high resolution structural imaging without exogenous labels in living muscle cells. This may be very important for detecting changes in myofibrillar organization occurring under pathophysiological conditions, e.g., in cardiac and skeletal myopathies. Due to the strong dependency of SHG on orientation and symmetries of the tissue, it may allow the study of dynamic interactions between the contractile proteins actin and myosin during force production and muscle shortening. Furthermore, SHG imaging can be combined with other nonlinear microscopical techniques, such as laser scanning multiphoton fluorescence microscopy, to simultaneously measure other dynamic cellular processes, representing a complementary method and extending the range of nonlinear microscopical methods.
Gesehen am 27.04.2021